Konsep Pembentukan Karakter di Era Modern Dalam Pandangan Filsafat Pendidikan Islam - Zahra, Mutia; Aini, Avivah Nur; Azmiwardani, Imelia Nur (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Personality is an important aspect of education and is essential in forming quality human beings and plays an important role. In the context of Islamic educational philosophy, the concept of character education has become the center of attention in modern times to understand how Islamic values can be put into practice in the educational process. This research aims to determine the research methods used to analyze the nature of personality and understand its concepts from a philosophical point of view. This research uses a qualitative approach with library research methods. The library method (library study) is a data collection method carried out by reading, taking notes and analyzing books, journals and scientific articles that are relevant to the research topic. The findings of this research provide in-depth insight into the concept of character education in contemporary Islamic education.